Industrial Internet of Things enabled technologies, challenges, and future directions - Shams Forruque Ahmed (16517712) (2023)
The Industrial Internet of Things (IIoT) is recognized as the fourth industrial revolution as it enhances productivity, dependability, and competitive performance by concentrating on profitability. IIoT-enabled technologies have been reviewed and implemented in several research, but more research into the opportunities and challenges they present is necessary. This paper explores IIoT-enabled technologies and infrastructure, their role in global industrial growth, applications, challenges, and future directions. IIoT applications use the intelligence of things to solve industrial problems like supply chain mismanagement, data privacy risks, a weak cloud strategy, cost containment, and others. For instance, fog computing reduces parking, platform, fuel, and CO2 emissions. A blockchain-based security framework for the cement sector can resolve 51% of security issues and Sybil attacks caused by consensus algorithms like Proof of Work (PoW). Major companies' performance depends on well-designed IIoT infrastructure, despite significant challenges. Industrial technologies will improve as research and experimentation advance IIoT infrastructure.  Other Information Published in: Computers and Electrical Engineering License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://doi.org/10.1016/j.compeleceng.2023.108847